Workplace Spirituality as Mediator the Influence of Leadership Style on Employee Performance - Ekowati, Vivin Maharani (MEC-J (Management and Economics Journal), 2022)
This study aims to know the direct effect of leadership style on employee performance and test and analyze workplace spirituality's role as a mediator influencing leadership style to performance of employees. The target population of this study was employees of Indonesian Islamic banks in Malang Raya, totaling 310 employees. Sampling was done by proportional random sampling, using Slovin formula with a tolerable error rate of 10 percent, then obtained a total sample of 76 employees. Data were collected directly from respondents using a questionnaire instrument. The data analysis technique used is Path Analysis. The results of the study prove that leadership style has a significant effect on employee performance. Workplace spirituality mediates influence leadership style on employee performance.